Formulation of Antioxidant Emulgel containing Beluntas China (Gynura pseudochina (L.) DC) - Fitriani Jati Rahmania; Marline Abdassah; Muhaimin Muhaimin; Anis Yohana Chaerunisaa (Universitas Padjadjaran (Unpad), 2020)
Skin constantly exposed by the environmental stresses, such as pollutants, solar radiation, heat, and cold, which cause the free radicals that cause premature aging. This bad effects of free radicals can be reduced by natural antioxidants such as Beluntas china (Gynura pseudochina (L.) DC) extract. The antioxidants use of beluntas china extract for skin will be more optimal if it is applied by appropriate form, emulgel, which has stronger consistency and longer contact time than gel. The aim of this research was to formulate an antioxidant emulgel from beluntas china extract, which is effective, stable, and safe with the best gelling agent. The extract was formulated by variety types of gelling agents which were carrageenan, hydroxypropyl methylcellulose (HPMC), and carbomer 934. Then, the physical stability was evaluated, including organoleptic, homogeneity, pH, viscosity, and freeze thaw. The results showed that formulation of carbomer 934 1% 2xIC50 extract concentration give the best physical stability evaluation for 60 days storage time.Keywords: antioxidant, beluntas china extract, emulgel, free radicals, skin